The geology and mineral resources of the neighbourhood of Bentong, Pahang and adjoining portions of Selangor and Negri Sembilan, incorporating an account of the prospecting and mining activities of the Bentong District - 362317 Alexander, J. B. (Ipoh : Geological Survey Headquaters, 1968)
08